2021
DOI: 10.3390/su13094908
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Teachers’ Training in Attention to SEN Students: Testing a Mediation Model

Abstract: There is growing interest in analyzing the evolution of inclusive education in universities, highlighting the training of teachers as the main barrier to this evolution. The purpose of this study was to analyze, through a mediation model, to what extent the accessibility and inclusion of university campuses affect, both directly and indirectly, the continuous training of teachers in attention to diversity and training demands by teachers in this same area. Participants were 580 teachers from the Faculty of Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…These courses should meet diverse objectives and cover varying degrees of complexity and themes. Universities must have teachers with inclusive profiles who are interested in continuous training [17]. In fact, González-Castellano et al [17] showed that the more accessible and inclusive the universities are, the more continuous training teachers have and therefore the more interest they have in continuing training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These courses should meet diverse objectives and cover varying degrees of complexity and themes. Universities must have teachers with inclusive profiles who are interested in continuous training [17]. In fact, González-Castellano et al [17] showed that the more accessible and inclusive the universities are, the more continuous training teachers have and therefore the more interest they have in continuing training.…”
Section: Discussionmentioning
confidence: 99%
“…Universities must have teachers with inclusive profiles who are interested in continuous training [17]. In fact, González-Castellano et al [17] showed that the more accessible and inclusive the universities are, the more continuous training teachers have and therefore the more interest they have in continuing training. Ortiz Colón et al [19] also confirm the need for training in special needs processes to enable university teaching staff to participate in an inclusive model and reveal the teaching staff do not consider themselves sufficiently prepared to provide an educational response to students with a disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, una menor cantidad de artículos mostraron actitudes positivas, lo que denota una mejor formación e interés del profesorado para promover una enseñanza inclusiva dirigida a todo el estudiantado. Los hallazgos encontrados concuerdan con distintos trabajos realizados concernientes a la temática (Avramidis & Norwich, 2002;González-Castellano et al, 2021;Moriña, 2020;Sánchez Díaz & Morgado Camacho, 2021).…”
Section: Actitud Docente Hacia La Inclusión Educativaunclassified
“…Professors’ attitudes towards integration reflect a lack of confidence in their instructional skills due to initial training received by future professors [ 22 , 23 ]. In line with this, a descriptive study [ 24 ] collects information about some adaptations that university professors carry out and the perception of their ability to carry out these adaptations.…”
Section: Introductionmentioning
confidence: 99%